Effects of two-step sintering on the properties of hydroxyapatite bioceramic - Ramesh S.; Gan C.J.; Bang L.T.; Niakan A.; Tan C.Y.; Purbolaksono J.; Chandran H.; Ramesh S.; Yap B.K.; Teng W.D. (Hanyang University, 2023)
In the present study, the sintering behaviour of hydroxyapatite (HA) was investigated by employing the two-step and conventional sintering methods. Comparisons were made between different combinations of sintering temperatures to examine their influence on the sinterability of the samples. The sintered samples were examined in terms of phase stability, relative density, grain size, Vickers hardness, and fracture toughness. The results revealed that the two-step sintering cycle was effective in suppressing grain coarsening when compared to conventional sintering. The study also found that while employing the twostep sintering, the selected temperature (T1) at which densification occurs plays a major role in determining the mechanical properties of HA samples. 2015, Hanyang University. All rights reserved.